Synthesis and structure of copper(II) complexes with 1-iso-propyl-1Н-1,2,4-triazole - Degtyarik, Mikhail M.; Bogatikov , Andrey N.; Voitekhovich , Sergei V.; Lyakhov , Alexander S.; Ivashkevich , Ludmila S.; Grigoriev , Yuri V.; Ivashkevich , Oleg A. (Journal of the Belarusian State University. Chemistry, 2020)
A novel facile method for the synthesis of 1-iso-propyl-1H-1,2,4-triazole (L) is described. This method is based on alkylation of 1,2,4-triazole with isopropyl alcohol in sulfuric acid media. It allows to synthesize the target product selectively with a yield of near 98 %. New coordination compounds [CuL2(Н2О)2Cl2] and [СuL4Cl2] were synthesized by the interaction of 1-iso-propyl-1H-1,2,4-triazole with copper(II) chloride dihydrate. Composition and structure of prepared complexes were studied by elemental analysis, X-ray diffraction analysis and IR spectroscopy. Both coordination compounds were found to be mononuclear complexes with octahedral coordination of copper atoms. Ligand L shows monodentate coordination through the triazole ring N4 atom. The analysis of the changes observed in the IR-spectrum of L under coordination with CuII atom was carried out. It was shown that IR spectroscopy can be used in order to study some structural peculiarities of azole complexes, in particular presence of bounded or coordinated water molecules and hydrogen bonds as well as localization of coordination bonds.